E-governance in developing countries: a case study of E-Disha initiative in the Indian state of Haryana. (2016) - Sharma, Tejinder; Mangalaraj, George; Natarajan, Vivek S.
Technological interfaces are increasingly being used, throughout the world, to reach out to larger sections for the delivery of e-governance services. Inadequacy of digitisation of records of the subsistence level citizens, lack of awareness of their rights, and little understanding of the processes to avail the governance services hamper the effectiveness and of delivery of the e-governance services to them. The study explores the adoption of E-Disha services by the subsistence level citizens, offered by the north-Indian state of Haryana. Findings indicate that the subsistence level citizens easily learn the use of technology-assisted interfaces and the E-Disha services measure up to the citizens' expectation on the dimensions of spatial convenience, ease of use, cost, and trust. By adopting a marketing and customer service paradigm, considering governance as a service and leveraging technology as a facilitator, the subsistence marketplaces could be better served and foster their inclusiveness into the social mainstream.